2019
DOI: 10.1007/978-3-030-13876-9_31
|View full text |Cite
|
Sign up to set email alerts
|

Thermonuclear Supernovae: Prospecting in the Age of Time-Domain and Multi-wavelength Astronomy

Abstract: We show how new and upcoming advances in the age of timedomain and multi-wavelength astronomy will open up a new venue to probe the diversity of SN Ia. We discuss this in the context of the ELT (ESO), as well as space based instrument such as James Webb Space Telescope (JWST). As examples we demonstrate how the power of very early observations, within hours to days after the explosion, and very late-time observations, such as light curves and mid-infraread spectra beyond 3 years, can be used to probe the link … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It emerges from the fitting when introduced as an additional free parameter not included in the hydrodynamical model. Possible physical causes may include a short-lived interaction between the SN ejecta with a low-mass accretion disc (Gerardy et al 2007 ) or a companion star (Marietta et al 2000 ), or surface burning as found in sub-M Ch explosions (Shen et al 2012 ) but see item (3), or the imprint of the burning of H/He-rich material originating from the surface (Hoeflich et al 2019 ). Interaction with a donor star seems less likely because it would affect not only the outermost layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It emerges from the fitting when introduced as an additional free parameter not included in the hydrodynamical model. Possible physical causes may include a short-lived interaction between the SN ejecta with a low-mass accretion disc (Gerardy et al 2007 ) or a companion star (Marietta et al 2000 ), or surface burning as found in sub-M Ch explosions (Shen et al 2012 ) but see item (3), or the imprint of the burning of H/He-rich material originating from the surface (Hoeflich et al 2019 ). Interaction with a donor star seems less likely because it would affect not only the outermost layers.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), corresponding to the very outer layers of ࣠ 4 × 10 −3 M ⊙ , making a sub-M Ch explosion an unlikely candidate even for the case of C/He mixtures (Shen & Moore 2014 ). Note that M Ch explosions may have a thin H/He-rich surface layer as a result of the accretion phase but at a significantly smaller mass, (1-5) × 10 −4 M ⊙ (Hoeflich et al 2019 ), an amount below our numerical resolution. Therefore, we neglect the H/He layer in our simulation.…”
Section: The R Efer Ence Modelmentioning
confidence: 99%
“…17 For example, to first order and as an upper limit, we may expect similar EC isotopes in HeD and DDT at 1.2 and 1.3 Me, respectively. However, the duration of compression by a detonation is shorter than the WD expansion timescale resulting in about one-half the shift in abundance with respect to from partial to NSE burning (log(ρ c )  −1), EC isotopes (log(ρ c ) ³ 8.5, 54 Fe, 57 Co, 58 Ni), and to increasingly neutron-rich isotopes from 55,56 Fe, 55 Mn to 48,52,54 Cr, 59,60 Fe (log(ρ c ) ³ 1.87), which is close to the accretion induced collapse (Höflich et al 1998b;Brachwitz et al 2000;Hoeflich et al 2019).…”
Section: Introductionmentioning
confidence: 68%
“…1). Geometry is sensitive to the companion star and the [7]. Middle: Temperature and turbulent velocity structure at the onset of thermonuclear runaway of the inner 100 km of a WD [8].…”
Section: Introductionmentioning
confidence: 99%
“…Figure1: Progenitor structure and multi-dimensional imprints. Upper left: Central WD density as a function of mass and the influence of element production[7]. Middle: Temperature and turbulent velocity structure at the onset of thermonuclear runaway of the inner 100 km of a WD[8].…”
mentioning
confidence: 99%